A history of youth justice in Ireland : opening up space in government - Sargent, Paul (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2010)
This thesis outlines a history of juvenile justice in Ireland. However, it does not amount to a straightforward narrative history, rather, it draws inspiration from the later writings of Michel Foucault, specifically his essay ‘Governmentality’ (1991a). Here Foucault highlights the transition that takes place in the eighteenth century from the ‘art of government’ to ‘political science’. This science involves all the institutions, forms of knowledge, techniques and tactics that constitute the ‘mentality’ to govern. After Foucault, a rich vein of literature utilising the concept of ‘governmentality’ emerged and this thesis draws from and engages with this literature, especially that developed by Mitchell Dean and Nikolas Rose.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin